Pay Settlements in Manufacturing Industry, 1979-84: A Micro-data Study of the Impact of Product and Labour Market Pressures. - Gregory, M; Lobban, P; Thomson, A (1987)
This paper uses survey data on pay settlements for individual bargaining groups to quantify the impact of a range of influences on pay increases. The level of profits emerges as consistantly the most important pressure, with lesser roles for the need to recruit or retain labor, the risk for redundancy, and price competitiveness; intracompany comparisons are the most important focus of comparability pressures, while the impact of industrial action is detectable but limited. Panel data are used, and estimation is by the Seemingly Unrelated Regressions method.